2001
DOI: 10.1176/appi.ajp.158.7.1067
|View full text |Cite
|
Sign up to set email alerts
|

A Placebo-Controlled Study of Guanfacine in the Treatment of Children With Tic Disorders and Attention Deficit Hyperactivity Disorder

Abstract: Guanfacine appears to be a safe and effective treatment for children with tic disorders and ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
297
2
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 507 publications
(312 citation statements)
references
References 54 publications
8
297
2
5
Order By: Relevance
“…Another alpha-2 agonist, guanfacine, was studied in a randomized clinical trial with 34 children with ADHD and chronic tic disorder. At doses ranging from 1.5 to 3 mg per day given in three divided doses, guanfacine was superior to placebo for ADHD symptoms and tics [41].…”
Section: Medications For Tsmentioning
confidence: 92%
See 1 more Smart Citation
“…Another alpha-2 agonist, guanfacine, was studied in a randomized clinical trial with 34 children with ADHD and chronic tic disorder. At doses ranging from 1.5 to 3 mg per day given in three divided doses, guanfacine was superior to placebo for ADHD symptoms and tics [41].…”
Section: Medications For Tsmentioning
confidence: 92%
“…In addition, a conservative approach to dosing of the stimulant as well as combined use of an alpha-2 agonist may reduce the likelihood of tic worsening. Nonstimulant medications such as guanfacine or atomoxetine should be considered for children with ADHD who cannot tolerate stimulant medications [41] [42].…”
Section: Medications For Tsmentioning
confidence: 99%
“…It has been reported that clonidine and guanfacine are effective for treatment of human psychiatric disorders that involve PFC dysfunctions, such as attention-deficit/hyperactivity disorder (ADHD) (Arnsten et al, 1996;Arnsten and Li, 2005;Chappell et al, 1995;Hunt et al, 1995;Scahill et al, 2001;Taylor and Russo, 2001), schizophrenia (Friedman et al, 2001(Friedman et al, , 2004 and post-traumatic stress disorder (Horrigan, 1996;Porter and Bell, 1999). Atomoxetine is a reuptake inhibitor of norepinephrine (NE) and has also been used for treatment of ADHD (Gilbert et al, 2007;Perwien et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These results verify the feasibility and acceptability of treating ADHD by stimulating α 2A -adrenoceptors in the PFC or up-regulating the NE concentration in synapses and extrasynaptic space in the PFC. Actually, the α 2A -adrenergic agonists guanfacine and clonidine have been used experimentally and clinically to treat ADHD [92][93][94][95][96][97] . The selective inhibitor of the NE transporter atomoxetine (tomoxetine or LY139603) has also been reported to alleviate ADHD symptoms [98] .…”
Section: N Ew Insights To Develop a Primate Model Of Adhdmentioning
confidence: 99%